Rock Fracture Response Exposed to Hydraulic Fracturing: Insight into the Effect of Injection Rate on Aperture Pattern - Bo Zhang; Xinyi Cui; Linjun Wang; Xiaodi Fu (Advances in Materials Science and Engineering)
Injection rate is critical to hydraulic fracturing operation, especially to the hydraulic fracture aperture, which affects the proppant and methane migration. In this study, hydraulic fracturing experiments were carried out on shale specimens to investigate the influence of injection rate on hydraulic fracture aperture. According to the experimental results, when the injection rate increases, the average aperture of hydraulic fracture shows a significant linear increase. For different injection rate, the average aperture of stimulated natural fracture is always slightly greater than that of newly opened fracture. Compared with a low injection rate, the fracture apertures induced by the largest injection rate are evenly distributed in more intervals and approximately conform to the normal distribution. The research results can provide a theoretical basis for enhancing the fracture conductivity of hydraulic fracturing in shale reservoirs.